Decree of the President of the Arab Republic of Egypt No. 184 of the Year 2013 Concerning the Issue of the Customs Tariff = قرار رئيس جمهورية مصر العربية رقم 184 لسنة 2013 بإصدار التعريفة الجمركية - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.